2019
DOI: 10.3892/mmr.2019.10356
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of P2Y2 and HuD during the development of the enteric nervous system in fetal rats with anorectal malformations

Abstract: Certain patients with anorectal malformations (ARMs) continue to suffer from postoperative dysphoria. The enteric nervous system (ENS) is closely associated with defecation. The purinergic receptor P2Y2 (P2Y2) and Hu antigen D (HuD) proteins contain multiple motifs that enable their activation and direct coupling to integrin and growth factor receptor signaling pathways; thus, they may serve as key points in ENS development. The aim of the present study was to investigate the expression pattern of P2Y2 and HuD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…China was the second most productive country on ARM research. Chinese studies reported frequently on basic ARM research including genetic pathways in animal models or the evolution of single-incision laparoscopic approaches to ARM [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The high number of Japanese papers may be explained by the establishment of the Japanese Group for the Study of Anorectal Anomalies (JGSA) in 1974.…”
Section: Discussionmentioning
confidence: 99%
“…China was the second most productive country on ARM research. Chinese studies reported frequently on basic ARM research including genetic pathways in animal models or the evolution of single-incision laparoscopic approaches to ARM [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The high number of Japanese papers may be explained by the establishment of the Japanese Group for the Study of Anorectal Anomalies (JGSA) in 1974.…”
Section: Discussionmentioning
confidence: 99%
“…Hud can promote the mitosis of neural stem cells, and it is an important protein involved in the differentiation and maturation of neurons (59). HuD is abundantly expressed in the healthy ENS and its expression is decreased in diseased tissues with loss of intestinal function (49).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a high expression level of HuD is correlated with many diseases, especially aging diseases such as Alzheimer's disease and insulin insufficiency 8–10 . Meanwhile, scientists have found that a high expression level of HuD also plays an important role in the progression and metastasis of cancers such as oral squamous cell cancers, rectal cancer, and small cell lung cancer 11–13 . These findings reveal that HuD is related to organism aging, which is not only a marker to judge the prognosis of the disease, but also a potential target for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has also been reported that HuD over‐expression plays a certain role in the progression and aggravation of some cancers, especially in oral squamous cell cancer, rectal cancer, and small cell lung cancer 11–13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation